Terms of Trade Shocks and Economic Recovery - Imam, Patrick (IMF Working Papers; Working Paper, 2008)
This paper identifies factors that contribute to a fast recovery in growth after persistent negative terms of trade shocks, using a sample of 159 countries for 1970-2006. The results suggest that policies matter. Fast recoveries are fairly robustly related to real exchange rate depreciation and improvements in government stability and the institutional environment. A timely increase in aid may also support recovery.